Asymmetric synthesis of β-amino cyanoesters with contiguous tetrasubstituted carbon centers by halogen-bonding catalysis with chiral halonium salt - Yoshida, Yasushi; Aono, Maho; Mino, Takashi; Sakamoto, Masami (Beilstein Journal of Organic Chemistry, 2025)
β-Amino cyanoesters are important scaffolds because they can be transformed into useful chiral amines, amino acids, and amino alcohols. Halogen bonding, which can be formed between halogen atoms and electron-rich chemical species, is attractive because of its unique interaction in organic synthesis. Chiral halonium salts have been found to have strong halogen-bonding-donor abilities and work as powerful asymmetric catalysts. Recently, we have developed binaphthyl-based chiral halonium salts and applied them in several enantioselective reactions, which formed the corresponding products in high to excellent enantioselectivities. In this paper, the asymmetric synthesis of β-amino cyanoesters with contiguous tetrasubstituted carbon stereogenic centers by the Mannich reaction through chiral halonium salt catalysis is presented, which provided the corresponding products in excellent yields with up to 86% ee. To the best of our knowledge, the present paper is the first to report the asymmetric construction of β-amino cyanoesters with contiguous tetrasubstituted carbon stereogenic centers by the catalytic Mannich reaction.
Keywords: asymmetric catalysis; chiral halonium salt; contiguous stereocenters; halogen bonding; Mannich reaction